Attention-Deficit Hyperactivity Disorder in Childhood Epilepsy - Randula Ranawaka; Kosala Karunaratne; DSG Mettananda (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2016)
Introduction: Attention-Deficit Hyperactivity Disorder (ADHD) is a recognized cause of learning impairment in children. Several studies have shown that there is an increased prevalence of ADHD in children with epilepsy. Objectives: To determine the prevalence of ADHD and its associations in children with epilepsy in a secondary care referral centre.                                                                                                                  To analyze the clinical characteristics of epileptic patients in the study group. Methods: A cross-sectional analytical study was conducted at the General Hospital, Chilaw, Sri Lanka in September 2012. All patients aged over 3 years with a confirmed diagnosis of epilepsy for at least 1 year were recruited into the study until a sample size of 100 was achieved. Data were collected using a pre-tested interviewer administered questionnaire. ADHD was defined using Diagnostic and Statistical Manual (DSM-IV) diagnostic criteria. Chi-square test and multiple logistic regressions were used in the analysis. Results: Sixty-one percent of the study populations were males. Seventy-four patients had generalized epileptic seizures and 26 patients had partial epileptic seizures. Twenty-nine (29%) of patients had ADHD. Male sex, partial epileptic seizure type, duration of epilepsy over 5 years and use of more than one anti-epileptic drug were significantly associated with increased risk of having ADHD. Having partial epileptic seizures and use of more than one antiepileptic agent were independent predictors for the development of ADHD in multiple logistic regression. Conclusions: More than one-fourth of epileptic children in this study had associated ADHD. Male sex, partial epileptic seizure type, duration of epilepsy over 5 years and use of more than one antiepileptic drug were significantly associated with ADHD.